The Details of the Life of Ragusian Merchant and ‘Diplomat’ in Bosnia: Zhivan Pripchinovich (? -1479) - Hodžić, Muamer (Prilozi za orijentalnu filologiju, 2017)
This paper aspires to point out the importance and role of individual traders in the social relations between Dubrovnik and Bosnian hinterland through different events in which the principal, or one of the main actors is Zhivan Pripchinovich. Although the wider area as early as the second half of the fifteenth century was extremely unstable, there were people like Zhivan Pripchinovich who managed to connect people and their interests on both sides. With his effort Zhivan managed to influence not only his countrymen and the Bosnians but also later on the Ottoman authorities. Through his example we can see that the merchants were not just ordinary traders, but they were diplomats, negotiators, the rescuers from slavery and the occasional spies. Engaging in trade has brought a large and relatively quick profit, and influence in society, but not to all. Some of them are like Zhivan, despite large profits and the impact in society, due to the delinquent debts lost their lives.